Water quality assessment of an urban stream in Lages, Brazil, through analysis of water physicochemical properties and study of benthic macroinvertebrate communities - Cardoso, Josiane Teresinha; Girotto, Sandy Bernardi Falcadi Tedesco; Silva, Flávia Arcari da; Schein, Viviane Aparecida Spinelli; Leite, Daiana Petry (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
Urban growth causes environmental problems such as water contamination which, in turn, affects aquatic organisms and human populations. This work presents a study of an urban stream in Lages, SC, Brazil, hit by continued sewage discharge along part of its course. Through analysis of physicochemical and biological parameters, the water was classified according to the CONAMA Resolution 357/05 and the BMWP’ index. Samples were collected 5 times over one year at 5 sites: 2 sites upstream the area of sewage discharge, 2 sites in the area, and 1 site downstream the area. Dissolved oxygen, temperature, pH, phosphate, colour, and turbidity were the analysed physicochemical parameters. Benthic mocroinvertebrates were utilized for the biologic analyses. The sites upstream the area of sewage discharge presented the highest BMWP’ and diversity indices, highest dissolved oxigen rates, and the lowest concentration of total phosphorus. Water at these sites was ranked class 1. The other sites, in and downstream the area of sewage discharge, presented the lowest dissolved oxygen rates, high total phosphorus and turbidity values, and the lowest diversity and uniformity values. Water at these sites was ranked class 4 (polluted). Data analysis is in agreement with the degree of pollution observed along the stream, which undergoes anthropogenic impacts from source to canalization.